Judicial Attitude To Environmental Litigation And Access To Environmental Justice In Nigeria: Lessons From Kiobel - Mmadu, Rufus Akpofurere (Journal of Sustainable Development Law and Policy, 2025)
This paper examines judicial attitude to environmental litigation and access to environmental justice in Nigeria. The paper employs expository analysis as its methodology in discussing the theme. Essentially, the paper finds that environmental litigations in Nigeria are bedeviled by legal technicalities such that victims of environmental pollution and degradation are ultimately denied access to justice. Ranging from issue of locus to territorial and subject matter jurisdiction, victims of oil spill and environmental degradation are often left without judicial remedies. The paper finds that consequently, the people of the Niger Delta are increasingly losing confidence in the judiciary both at the domestic and international level. This has heightened militancy and youths’ restiveness in the area leading to loss of revenues and sometimes lives. The paper notes with concern the recent trend of outsourcing justice, as evident in attempts to bring environmental pollution cases in Nigeria before domestic courts abroad. For example the celebrated case of Kiobel v Royal Dutch Shell, heard in United States of America. Kiobel is arguably a setback to this approach of searching for environmental justice before international courts and a reminder on the need to look inwards. This paper calls for judicial flexibility and a more proactive approach to legal reasoning by Nigerian courts, in order to put environmental matters on the front burner of our national discourse. Unless and until environmental justice is entrenched in Nigeria through judicial activism, Governmental inertia and unwillingness to provide remedies for victims of environmental degradation may continue to fuel militancy in the years ahead.